Disease Control Priorities, Third Edition : Volume 2. Reproductive, Maternal, Newborn, and Child Health - Black, Robert; Laxminarayan, Ramanan; Temmerman, Marleen; Walker, Neff (Washington, DC: World Bank, 2016)
This book focuses on maternal conditions, childhood illness, and malnutrition. Specifically, the chapters address acute illness and undernutrition in children, principally under age 5. It also covers maternal mortality, morbidity, stillbirth, and influences to pregnancy and pre-pregnancy. It also includes the transition to older childhood, in particular, the overlap and commonality with the child development volume.